Textbooks: Malvinas and Antarctica to the “New Argentina” of Perón - Garcia, Amelia Beatriz (Universidade Estadual de Londrina, 2009)
The investigation on the image of the Patagonia realized across the school texts narrowly linked to the pedagogic offers and to the political intentions, allows to identify a fan of representations translated in these terms: the indigenous and desert Patagonia, the petroliferous Patagonia, the tourist Patagonia resembled the Switzerland Argentina, to which the Patagonia adds as end of the Mother land that prolongs the Patagonian extension up to the Antarctica and Islands of the Atlantic Ocean South. Continuing the line of analysis, this article we deal with a particularly controversial claim and the issue of possession of Antarctica and the Malvinas Islands as an objective of state policy for territorial integration. That policy, in this case, refers to the period 1946-1955 which corresponds to the presidency of Gral. Juan D. Peron. The actions of this government on the rights of the southern lands were part of the content to be included in textbooks and such content simultaneously figured prominently to introduce the doctrinal principles Peronist. La investigación sobre la imagen de la Patagonia realizada a través de los textos escolares, estrechamente vinculados a las propuestas pedagógicas y a las intenciones políticas, permite identificar un abanico de representaciones traducidas en estos términos: la Patagonia indígena y desierta, la Patagonia petrolífera, la Patagonia turística, asimilada a la Suiza Argentina, a la que se suma la Patagonia como fin de la Patria que prolonga la extensión patagónica hasta la Antártida e Islas del Atlántico Sur. Continuando con la línea de análisis, en este artículo nos ocupamos de un tema especialmente controvertido: la cuestión del reclamo y posesión de la Antártida e Islas Malvinas como objetivo de las políticas de Estado respecto de la integración territorial. Tal política, en este caso, está referida al período 1946-1955 que se corresponde con la presidenci del Gral. Juan D.Perón. Las acciones de este gobierno acerca de la defensa de los derechos sobre las tierras ...